Access to health services in the southern outskirts of the Brazilian Federal District - Ana Cléia Margarida Tonhá; Paulo Roberto Borges de Souza Júnior; Ana Lucia Queiroz Bezerra; Thays Angélica de Pinho Santos; Claci Fátima Weirich Rosso (Universidade Federal de Goias, 2015)
The aim of this study was to analyze people's perception on the access to health services in the southern outskirts of the Integrated Region for the Development of the Federal District (RIDE/DF, as per its acronym in Portuguese). A descriptive, cross-sectional, epidemiological and population-based study with a household survey design was carried out in 2010 and 2011. A semi-structured questionnaire, previously validated, was applied. A total of 605 individuals who lived in the southern outskirts of the Federal District were interviewed, of which 311 (51.4%) were female, 215 (35.8%) had incomplete primary education, 163 (40.9%) sought health services in Primary Care Units and 166 (45.5%) sought health services in another municipality. Access to health services in the region is influenced by social and economic conditions and by the place of living. These findings allow managers to better study the setting, review care services provided and meet health needs of that population.